The Effect of Determining Import Duty Rates and Free Trade Facilities Schemes on State Revenue at KPPBC TMP Belawan by The Functional Officer of Document Examination for Imports - Mayana, R. Virdi; Lubis, Zulkarnain; Siregar, Nina Siti Salmaniah (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to analyze the effect of determining import duty rates and free trade facility schemes on state revenues at the Belawan Customs, Excise, and Tax Services Office (KPPBC) Postal Inspection Place (TMP) by functional officials checking documents for imports. The research method used is descriptive research with a quantitative approach. The data used is secondary data obtained from KPPBC TMP Belawan as well as primary data obtained through interviews and documentation studies. Data analysis was carried out using a simple linear regression technique to test the influence of import duties and free trade facility schemes on state revenues. The research results show that the determination of import duty rates and free trade facility schemes has a significant influence on state revenues at KPPBC TMP Belawan. Setting low import duties and providing adequate free trade facilities can increase state revenues through import activities carried out by business actors in the region. The implication of this research is the importance of appropriate import duty tariff policies and the provision of free trade facilities that can encourage economic growth and state revenues in the KPPBC TMP Belawan area.